GROWTH PERFORMANCE OF THE RING-NECKED PHEASANTS (Phasianus colchicus Linnaeus, 1758) IN INDOOR CONDITIONS IN HUE CITY, THUA THIEN HUE PROVINCE - Trung, Nguyễn Trần; Dung, Trần Quốc; Mai, Nguyễn Thị; Phong, Bùi Anh (Hue University Journal of Science: Natural Science, 2017)
Newborn ring-necked pheasants (Phasianus colchicus Linnaeus, 1758) were kept for 24 weeks in an indoor housing in Hue city, Thua Thien Hue province, Vietnam. The pheasants were fed on Con-co compound (P221 and P222). The body weight was determined at the end of every week of rearing. Six pheasants were selected for slaughter at the end of the 24th week and the carcass was evaluated. The results showed that the survival rate after 24 weeks was 80 %; the body weight was 1296.18 g/bird. The absolute growth and relative growth were 7.45 g/bird/day and 17.15 %, respectively. Higher body weights and daily gains were found in males than in females on all test days during rearing for 24 weeks. The carcass rate of the ring-neck pheasant was 76.42 %; the breast muscles rate was 19.38 %; the leg muscles rate was 8.67 %, and the abdominal fat rate was 0.98 %. The feed conversion ratio was 8.07 kg/kg and the feed intake was 48.01 g/bird/day.